Donor Small-Droplet Macrovesicular Steatosis Affects Liver Transplant Outcome in HCV-Negative Recipients - Flaminia Ferri; Quirino Lai; Antonio Molinaro; Edoardo Poli; Lucia Parlati; Barbara Lattanzi; Gianluca Mennini; Fabio Melandro; Francesco Pugliese; Federica Maldarelli; Alessandro Corsi; Mara Riminucci; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background. No data are available on liver transplantation (LT) outcome and donor liver steatosis, classified as large droplet macrovesicular (Ld-MaS), small-droplet macrovesicular (Sd-MaS), and true microvesicular (MiS), taking into account the recipient Hepatitis C virus (HCV) status. Aim. We investigate the impact of allograft steatosis reclassified according to the Brunt classification on early graft function and survival after LT. Methods. We retrospectively reviewed 204 consecutive preischemia biopsies of grafts transplanted in our center during the period 2001-2011 according to recipient HCV status. Results. The median follow-up after LT was 7.5 years (range: 0.0-16.7). In negative recipients (n=122), graft loss was independently associated with graft Sd-MaS, in multivariable Cox regression models comprehending only pre-/intraoperative variables (HR=1.03, 95%CI=1.01-1.05; P=0.003) and when including indexes of early postoperative graft function (HR=1.04, 95%CI=1.02-1.06; P=0.001). Graft Sd-MaS>15% showed a risk for graft loss > 2.5-folds in both the models. Graft Sd-MaS>15% was associated with reduced graft ATP content and, only in HCV- recipients, with higher early post-LT serum AST peaks. Conclusions. In HCV-negative recipients, allografts with >15% Sd-MaS have significantly reduced graft survival and show low ATP and higher AST peaks in the immediate posttransplant period. Donors with >15% Sd-MaS have significantly higher BMI, longer ICU stays, and lower PaO2.